A comparative study and investigation of different diode models incorporating the partial shading effects - Varshney, Santosh Kumar; Khan, Zeeshan Ahmad; Husain, Mohammad Aslam; Tariq, Abu (2016 International Conference on Electrical, Electronics, and Optimization Techniques (ICEEOT), 2016)
The paper holistically discusses the analysis and simulation of simplified two diode model and its comparative analysis with the one and three diode models. The two diode model presented has been grounded on the interpretation of the output current equation. This model entails four parameters and condenses the complexity and the computational time considerably. I-V and P-V curves for two diode model are plotted taking into account the variation of the atmospheric irradiance and temperature. Furthermore the two diode model is analysed by taking into account the effect of partial shading which plays an extremely detrimental role in the Solar Array output. A grave issue with partly shaded PV arrays is detouring of the maximum output voltage which acts to preponderate due to the manoeuvre of the bypass diodes present alongside the affected cell. This might cause a sizeable power loss, subject to the frequency of shading manifestation and thus leading to substantial reduction in the energy output of module. Paper presented scrutinizes the effects of six different Shading schemes on 6 × 6 array. Additionally it peers effects of Partial Shading on the different diode models in consideration. The characteristics of the diode models are comprehensively affected due to the presence of the shading effect. All the diode models for the investigation have been primed using the MATLAB simulation software. The values of various parameters used for comparison are presented in tabular form. The conclusions are deduced and the best model for simulation purpose is suggested taking into account the partial shading effect. From the outcomes and conclusions of this paper, it can be established that there exists a momentous loss in the output power because of the irregular irradiation pattern visible on the series strings.